{2-Morpholino-N- 1-(2-pyridyl)ethylidene ethanamine-kappa N-3,N ',N ''}bis(thiocyanato-kappa N)copper(II) - Gwaram, N.S.; Ali, Hapipah Mohd; Khaledi, H.; Hisham, N.A.I. (International Union of Crystallography, 2011)
In the title compound, [Cu(NCS)(2)(C13H19N3O)], the Cu-II ion is five-coordinated by the N,N',N ''-tridentate Schiff base and the N atoms of two isothiocyanate ligands in a square-pyramidal geometry. In the crystal, C-H center dot center dot center dot N, C-H center dot center dot center dot O and C-H center dot center dot center dot S interactions link adjacent molecules into layers parallel to the ac plane. A weak intermolecular pi-pi interaction occurs between the aromatic rings with a centroid-centroid distance of 3.9412 (9) angstrom.